ANTHROPOLOGICAL INTENTION OF PHILOSOPHIZING OF RENE DESCARTES AND ITS MANIFESTATION IN THE TEXT «THE RULES» - Anatolii Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2015)
Purpose. Based on the understanding of The New Time philosophy as a response to the challenges of the era in relation to the construction of an objective picture of the world and the self-creation of man, to analyze the main options for evaluating the ambivalence of the basic intention of the philosophy of Descartes in the research literature and to clarify the nature of ambiguity. To justify the dominant nature of anthropological intention in the text of the «Rules for Guiding the Mind in Searching for the Truth». Novelty. The nature of the ambivalence of the basic intention of the text of the "Rules" is clarified as a form of two basic existences, opposite to the New Time, namely the query on the objectivity of scientific knowledge and inquiry in anthropology as a cornerstone of philosophy. The author of the article proves the domination of anthropological component of the text «The Rules» in front of scientific knowledge. Conclusions. The main manifestations of ambivalence of basic directivity of philosophizing of Rene Descartes to construction of an objective picture of the world and self-creation of person were described. The determining influence on the process of the establishment of basic intention of the specificity of the experience of mathematical knowledge and Plato’s and Aristotle’s tradition of philosophizing for the first, and of personal tradition of Christianity in the second place was emphasized. In the reference to the text «The Rules» of Descartes the ambiguity of the basic direction was argued, the nature and domination of the anthropological intention were justified.